Managing Educational Knowledge Using Visual Ontologies - Gavrilowa, Tatiana; Jin, HaiNan (Studia Informatica. System and information technology, 2008)
Knowledge portal is an approach used to provide view onto domain-specific information on the World Wide Web. In this paper, we present one approach by using ontology engineering as a conceptual backbone and relationships for knowledge extracting, structuring and formalizing in a comprehensive way for building knowledge portal. For illustration of a practical ontology development for knowledge portal, the described ideas are implemented in a system for international student service.